Monitoring physiological responses and fluid balance of elite female beach handball players during an international tournament - Bayram Ceylan; M.K. Kerem; S.Ç. Çeyiz; V.V.G. Gürses; M.Ş.A. Akgül; B.B. Baydil (Physical Education of Students, 2020)
Background and Study Aim. Despite its increasing popularity, beach handball has not been studied in terms of physiological responses. Thus the aim of this study was to demonstrate lactate and heart rate responses as well as urine specific gravity (USG) levels and fluid intakes of female university students who competed at an international beach handball tournament.